IPCS mode of action framework (World Health Organization, 2007)
The use of structured frameworks in chemical risk assessment promotes transparent, harmonized approaches. This book presents two IPCS frameworks originally published in Critical Reviews in Toxicology, in a user-friendly large format. Part 1 contains the IPCS Framework for Analysing the Relevance of a Cancer Mode of Action for Humans, along with three case studies illustrating its application. Part 2 contains the IPCS Framework for Analysing the Relevance of a Non-Cancer Mode of Action for Humans. The output of a framework analysis is a clear statement of conclusions, together with the confidence analysis and implications of the findings. The framework provides a means of ensuring a transparent evaluation of the data identification of key data gaps and of information that would be of value in the further risk assessment of the chemical in question.
IPCS harmonization project document ; no. 4
Keywords: Hazardous Substances; hodnocení rizik; onkologie; řízení rizik; nebezpečné látky; nádory; testy karcinogenity; Neoplasms; karcinogeny; toxikologie; Carcinogens; Risk Management; Risk Assessment; Carcinogenicity Tests